2010
DOI: 10.1097/fjc.0b013e3181ee6811
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Stimulation of Proteoglycan Synthesis in Vascular Smooth Muscle is Mediated by Endothelin Receptor Transactivation of the Transforming Growth Factor-β Type I Receptor

Abstract: We utilized human vascular smooth muscle cells to address the question if a G-protein-coupled receptor, the endothelin (ET) receptor, could transactivate a serine/threonine kinase receptor, specifically the transforming growth factor (TGF)-[beta] receptor, T[beta]RI. Functionality of the interaction was addressed by studying endothelin-1-stimulated proteoglycan synthesis. Signaling molecules were assessed by Western blotting and proteoglycan synthesis by [35S]sulfate and 35S-met/cys incorporation and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 46 publications
0
78
0
Order By: Relevance
“…Here serotonin via its GPCR 5-hydroxytryptophan 1B/1D activates BMPR1A, leading to the rapid generation of phosphoSmad1, -5, and -8, which is also sensitive to ROCK inhibition, albeit a role for integrins was not examined (33). Our previous work has demonstrated that thrombin and endothelin-1 stimulate increases in phosphoSmad2(Ser465/467) in human VSMC similarly to that of mouse lung epithelial cells (8,9); however, until now the mechanism by which this is mediated was unknown. This study provides evidence that thrombin stimulates phosphoSmad2 in human VSMC via a similar mechanism to that in mouse lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here serotonin via its GPCR 5-hydroxytryptophan 1B/1D activates BMPR1A, leading to the rapid generation of phosphoSmad1, -5, and -8, which is also sensitive to ROCK inhibition, albeit a role for integrins was not examined (33). Our previous work has demonstrated that thrombin and endothelin-1 stimulate increases in phosphoSmad2(Ser465/467) in human VSMC similarly to that of mouse lung epithelial cells (8,9); however, until now the mechanism by which this is mediated was unknown. This study provides evidence that thrombin stimulates phosphoSmad2 in human VSMC via a similar mechanism to that in mouse lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ligand-independent activation of a receptor, known as transactivation, which has long been described for protein tyrosine kinase receptors (Correa-Meyer et al, 2002;Hua et al, 2003;Krepinsky et al, 2005a), has recently also been described for the TbR Little et al, 2010). Indeed, CTGF induction in myoblasts by the G-protein coupled receptor (GPCR) agonist LPA required TbRI transactivation (Cabello-Verrugio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a small molecule inhibitor is required in this area and potentially a modern drug discovery program directed at the YM-254890 or UBO-QIC structures might serve as a starting point. The need for a potent and efficacious agent is exemplified in the area of GPCR transactivation signalling where there is very little knowledge of the role of G proteins either in the long established transactivation of protein tyrosine kinase receptors or the more recently identified transactivation of serine/threonine kinase receptors [3,4,26]. The role of G proteins has not been described and potentially a common G protein dependent mechanism might represent a novel therapeutic target to block all of the responses attributable to GPCR transactivation signalling [27].…”
Section: Resultsmentioning
confidence: 99%